2022
DOI: 10.7759/cureus.32513
|View full text |Cite
|
Sign up to set email alerts
|

Cardio-oncology Clinical Assessment and Screening in Patients Undergoing High Toxicity Chemotherapy: A Retrospective Cohort Study

Abstract: Objective: To describe the clinical characteristics and cardio-oncological assessment in patients undertaking highly toxic chemotherapy and/or chest radiotherapy in a high-complexity hospital.Methods: A single-center retrospective cohort study was carried out between January 1st, 2017 and December 31st, 2019. The medical records of patients with solid or hematological neoplasms were reviewed. Descriptive information was obtained on demographic characteristics, chemotherapeutic agents, prechemotherapy cardiovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Real-world data from a recent retrospective cohort study showed that pre-chemotherapy echocardiography was obtained in 65% of patients, but only in 19% of them after completing chemotherapy. 33 Consequently, the feasibility of accurate and reproducible calculation of LVEF by oncology staff at the point of care shown in this study can have significant clinical implications. By using robust guiding and measurement AI algorithms, it could be applied as an initial screening tool pre- and post-chemotherapy for timely detection of cardiac dysfunction when SE examination is not readily available; this strategy could potentially expedite clinical care for cancer patients in case of impaired LVEF detection and speed up referral to a cardio-oncology clinic, where a more thorough cardiac evaluation beyond the mere LVEF measurement can be performed.…”
Section: Discussionmentioning
confidence: 86%
“…Real-world data from a recent retrospective cohort study showed that pre-chemotherapy echocardiography was obtained in 65% of patients, but only in 19% of them after completing chemotherapy. 33 Consequently, the feasibility of accurate and reproducible calculation of LVEF by oncology staff at the point of care shown in this study can have significant clinical implications. By using robust guiding and measurement AI algorithms, it could be applied as an initial screening tool pre- and post-chemotherapy for timely detection of cardiac dysfunction when SE examination is not readily available; this strategy could potentially expedite clinical care for cancer patients in case of impaired LVEF detection and speed up referral to a cardio-oncology clinic, where a more thorough cardiac evaluation beyond the mere LVEF measurement can be performed.…”
Section: Discussionmentioning
confidence: 86%
“…Chemotherapy-related cardiotoxicity gained significant emphasis as it has been linked to the risk of cardiac dysfunction, thromboembolic events, and arrhythmias, necessitating the implementation of effective prevention and treatment strategies [ 1 ]. Notably, cardiotoxicity has become more noticeable with the advancement of cancer screening and detection, along with the improvement of chemotherapeutic efficacy and overall prolonged survival [ 2 ].…”
Section: Introductionmentioning
confidence: 99%